Extended Kd distributions for freshwater environment. (December 2018) - Boyer, Patrick; Wells, Claire; Howard, Brenda
Abstract: Many of the freshwater K d values required for quantifying radionuclide transfer in the environment (e.g. ERICA Tool, Symbiose modelling platform) are either poorly reported in the literature or not available. To partially address this deficiency, Working Group 4 of the IAEA program MODARIA (2012–2015) has completed an update of the freshwater Kd databases and Kd distributions given in TRS 472 (IAEA, 2010). Over 2300 new values for 27 new elements were added to the dataset and 270 new Kd values were added for the 25 elements already included in TRS 472 (IAEA, 2010). For 49 chemical elements, the Kd values have been classified according to three solid-liquid exchange conditions (adsorption, desorption and field) as was previously carried out in TRS 472. Additionally, the K d values were classified into two environmental components (suspended and deposited sediments). Each combination (radionuclide x component x condition) was associated with log-normal distributions when there was at least ten K d values in the dataset and to a geometric mean when there was less than ten values. The enhanced K d dataset shows that K d values for suspended sediments are significantly higher than for deposited sediments and that the variability of K d distributions are higher for deposited than for suspended sediments. For suspended sediments in field conditions, the variability of K d distributions can be significantly reduced as a function of the suspended load that explains more than 50% of the variability of the K d datasets of U, Si, Mo, Pb, S, Se, Cd, Ca, B, K, Ra and Po. The distinction between adsorption and desorption conditions is justified for deterministic calculations because the geometric means are systematically greater in desorption conditions. Conversely, this distinction is less relevant for probabilistic calculations due to systematic overlapping between the K d distributions of these two conditions. Highlights: Solid-liquid fractionation of radionuclides in freshwater environments. Update of the freshwater K d databases for 49 chemical elements. Log-normal distributions of K d values. Mass/Volume ratio effect on K d distributions of suspended sediments in the field.